The coefficients of x inside the brackets are 4 and two - the expansion in the b position is then:
4x*3+2x*(-3)=6x, as shown.
How did this factorization come to be?
I see where 4x and 2x came from, and I under stand that -3*3=-9 for the C position, but how did the 6 get there in the B position? Isn't it supposed to be what you get when you add -3 +3? That would be 0, maybe something Im missing?
8x^2+6x-9
Factors of this equations are:
=> (4x-3)(2x+3)
Since the equation is related to factoring trinomials method i.e. ax^2+bx+c. Solve it by factorizing each term as :
8 can be factorize as 4 & 2. 6 can be factorize as 2 , 3 & -9 can be factorize as 3, -3. Now them accordingly to make equation balanced.
8x^2+6x-9
=> 8x^2+12x-6x-9
=>4x(2x+3)-3(2x+3)
=>(4x-3)(2x+3)
Thus the equation get its factors.